Practice beyond performance stabilization increases the use of online adjustments to unpredictable perturbations in an interceptive task - Crislaine Rangel Couto; Cláudio Manoel Ferreira Leite; Carlos Eduardo Campos; Leonardo Luiz Portes; Cíntia de Oliveira Matos; Suziane Peixoto Santos; Natália Fontes Alves Ambrósio; Hani Camille Yehia; Herbert Ugrinowitsch (PLoS ONE, 2025)
In recent decades, research has focused on motor adjustments in interception tasks within predictable environments. However, emerging studies suggest that continued practice beyond performance stabilization enhances the ability to adapt to unpredictable events. The objective of this study was to investigate the effects of practicing until performance stabilization versus extended practice through superstabilization on the ability to adjust to unpredictable perturbations in intercepting a moving target. We hypothesized superstabilization would better facilitate motor adjustments in response to unpredictable perturbations. Forty participants engaged in an interception task until they achieved either performance stabilization or superstabilization. Subsequently, both stabilization and superstabilization groups were tested in an unpredictable environment, where, in certain trials, the target’s velocity unexpectedly changed after the onset of the movement. The findings revealed that the superstabilization group made more adjustments, showing more number of corrections (N-cor), in response to these perturbations than the stabilization group, attributed to their developed capacity to use online feedback as a control mechanism more efficiently. In contrast, the practice until performance stabilization did not foster this adaptive mechanism. These results support the notion that learning is a dynamic process that extends beyond the point of performance stabilization, emphasizing the benefits of continued practice for mastering motor tasks in variable contexts.